Perceived stress and well-being of Polish migrants in the UK after Brexit vote - Martynowska, Klaudia (PLoS One, 2020)
OBJECTIVE: This study aimed to investigate factors affecting personal well-being of Polish immigrants living in the UK in the face of a significant political change—the Brexit vote. We measured perceived changes in attitude or behaviour of supervisors and co-workers, respondents’ perceived stress, and its outcomes such as psychological well-being and intention to leave the UK after the Brexit vote. METHOD: 551 Polish migrants residing in various regions of the UK took part in the study in the form of Qualtrics online survey. We used self-report measures: Perceived Stress Scale, The Satisfaction with Life Scale, Scale of Psychological Well-being. RESULTS: The most of the respondents did not notice any change in the attitude or behaviour of the supervisor (81%) or co-workers (84%), and only a small percentage of the participants reported negative changes in attitude or behaviour of supervisors (9%) and co-workers (14%). Also, negative change in attitude or behaviour of supervisors or co-workers are associated with perceived stress, which inturn is linked with intention to leave the UK, psychological well-being and life satisfaction. CONCLUSION: Polish and British co-existence in a workplace setting has not changed much after the Brexit vote.